Combinatorial effect of heat processing and phytic acid on mineral bioavailability in rice grain - Awadhesh Kumar; Milan Kumar Lal; Upasana Sahoo; Soumya Kumar Sahoo; Rameswar Prasad Sah; Rahul Kumar Tiwari; Ravinder Kumar; Srigopal Sharma (Food Chemistry Advances, 2023)
Brown rice is superior to milled rice in terms of bioactive compounds and minerals but also has phytic acid (PA) that may reduce the bioavailability of minerals. Further, various household cooking methods of rice also change the starch matrix, affecting mineral availability. The effect of PA and heat processing methods on Fe and Zn bioavailability from milled rice grain was investigated. Rice with contrasting PA was analyzed for Fe and Zn bioavailability in milled and cooked rice. The genotype Khira, with the lowest PA (2.0 g kg−1), exhibited high Fe and Zn bioavailability, while Phalguni, with the highest PA (11.2 g kg−1), showed low Fe and Zn bioavailability. The PA had a significant negative correlation with Fe and Zn bioavailability. Among three common household cooking methods used (pressure cooking, microwave-assisted cooking and boiling), pressure cooking exerted more remarkable effects on mineral bioavailability than other two methods. Screening rice genotypes for low PA and high Fe, Zn bioavailability can solve the problem of micronutrient malnutrition in countries where people depend on rice as the main staple food. The selection of appropriate cooking methods is also helps to enhance mineral bioavailability.